Development of high-temperature mini ceramic gas turbine rotor - Huang, Mingyue (2015)
Superalloys (Co, Cr, Ni-based alloy, and the others) have been widely used in aero-engine applications owing to their excellent performances at elevated temperature. But the intrinsic limitations of metals make it extremely difficult to achieve a higher turbine inlet temperature and a better engine efficiency. Thus, novel material candidates that can work at a higher temperature with the improved engine performances need to be explored, so as to satisfy the ever-increasing demands on the engine durability, energy saving and emission reduction in the aircraft engines. High temperature ceramics have prominent mechanical performance, excellent thermal and chemical resistance at the elevated temperatures due to the strong covalent and ionic bonds. The current research focuses on fabrication and characterization of mini ceramic turbine rotor through materials design and innovation to improve fuel efficiency and reduce carbon emission of mini jet engine. A mini alumina ceramic turbine rotor has been successfully fabricated using a tailored colloidal process based on gelcasting technology. A customized forming, drying method together with two-step sintering approach is developed for the complex-shaped component with both large volume (90 mm in diameter and 20 mm in height) and submillimeter geometry (0.42 mm at the curved blade tip), to assure a highly dense product without warpage and cracks. The effects of solid content and temperature on the rheological behaviors of the prepared slurry are investigated to identify the best pourability. The blade contour similarity is characterized by the proposed two-dimensional and three-dimensional imaging approaches under the different sintering strategies and solid contents. The physical and mechanical properties are discussed and their microstructures are analyzed. As the alternative strategies, the methods of Polyjet-mold and selective laser sintering were also adopted to fabricate the turbine rotor by depositing a sacriﬁcial polymeric mold and laser sintering Al2O3 and epoxy powders, respectively. A series of experiments on these rotor-forming routes are performed throughout the process, including the drying strategy, surface roughness, microstructure, mechanical properties, blade contour similarity, and so forth. Finally, the most suitable method to fabricate the complex-shaped alumina rotor with the best performances is recommended. In addition, advanced ceramic matrix composites have been developed. NiAl particles modified Al2O3 composites with toughening and crack healing performances are prepared. The toughening effects as a function of the particle size and content of NiAl compound are systematically investigated. In addition, the crack healing performance of the indented composites via oxidation of NiAl particles is evaluated at various temperatures in consideration of NiAl particle size. Atomic force microscope (AFM) is adopted to accurately characterize the healing process and explore the healing mechanism under each healing condition. The healing efficiency is quantitatively determined by using AFM imaged cracks. Furthermore, the tribological properties of this composite are discussed, and the results indicate a possible method to enhance the fracture resistance and wear performance of the NiAl/Al2O3 composites. Stress analysis by finite element analysis is performed to explore the stress distribution of the turbine rotor at various operating conditions. The effects of turbine inlet temperature, inlet pressure and rotor speed are respectively discussed to explore the ultimate operating conditions by considering the basic properties of rotor materials. The engine performances are compared between the commercial material Inconel 718 and the proposed alumina ceramics. The improved thermal efficiency verifies this research that ceramics have superior advantages in the gas turbine engine application on their light weights and excellent performances at the elevated temperatures.